Quadritherapy vs standard tritherapy immunosuppressant regimen after heart transplantation: A propensity score–matched cohort analysis. Issue 10 (17th April 2020) - Nguyen, Lee S.; Suc, Gaspard; Kheav, Vissal David; Coutance, Guillaume; Carmagnat, Maryvonnick; Rouvier, Philippe; Zahr, Noel; Salem, Joe‐Elie; Leprince, Pascal; Ouldammar, Salima; Varnous, Shaida
Abstract : After heart transplant, adding everolimus (EVL) to standard immunosuppressive regimen mostly relies on converting calcineurin inhibitors (CNIs) into EVL. The aim of this study was to describe the effects of combining low‐dose EVL and CNIs in maintenance immunosuppression regimen (quadritherapy) and compare it with standard tritherapy associating standard‐dose CNIs, mycophenolate mofetil, and corticosteroids. In the 3‐year registry cohort of heart transplanted patients, those who received quadritherapy were compared with those who received tritherapy. EVL was added after 3 months posttransplant. Three analyses were performed to control for confounders: propensity score matching, multivariable survival, and inverse probability score weighting analyses. Among 213 patients who were included (75 with quadritherapy), propensity score matching selected 64 unique pairs of patients with similar characteristics. In the matched cohort (n = 128), quadritherapy was associated with fewer deaths (3 [4.7%] vs 17 [21.9%], P = .007) and biopsy‐proven acute rejections (15 [23.4%] vs 31 [48.4%], P = .002). These results were confirmed in the overall cohort (n = 213), after multivariable and inverse probability score weighting analyses. Renal function and donor‐specific HLA‐antibodies remained similar in both groups. Low‐dose combination quadritherapy was associated with fewer deaths and rejections, compared with standard immunosuppression tritherapy. Abstract : Four‐ compared to three‐drug therapy is associated with fewer deaths and biopsy‐proven acute rejections in a cohort of heart transplant recipients.